Clinical and Histological Evaluation of Jaw Osteonecrosis Unrelated to Anti-Bone Resorption Drugs - Cinzia Casu; Andrea Butera; Andrea Scribante; Germano Orrù (Oral)
Medication-related osteonecrosis of the jaw (MRONJ) is a multifactorial condition defined as an adverse drug reaction that results in progressive jawbone destruction and necrosis in individuals treated with certain medications, occurring without a history of prior radiotherapy. These drugs are mainly bisphosphonates, denosumab, and other bone-modifying agents, anti-angiogenic agents such as anti-endothelial growth factor, tyrosine kinase inhibitors, and proteins classified as mammalian targets of rapamycin. The diagnosis of MRONJ is based on clinical (exposed jawbone, fistula with pus, hyperplasia of the mucosa overlying the necrotic bone tissue) and radiological evaluation. We report four cases of clinical and radiological evidence of osteonecrosis of the jaw that are unrelated to the use of antiresorptive or anti-angiogenic agents. In two instances, histological and microbiological evidence was also found (high concentration of Actinomyces, the microbe most commonly found in oral sites affected by MRONJ). These atypical cases are reported to highlight the possibility that other, previously undocumented, drugs may also contribute to the development of ONJ